Seeing The Spatial Readiness of Central Kalimantan as A Candidate For The Capital City Before The Decision of East Kalimantan as The New Capital - Abdul Qodir; Imam Qalyubi; Abubakar Abubakar; Misrita Misrita (Jurnal Syntax Transformation, 2023)
This paper describes how the data shows the readiness of Kalimantan candidates for capital city before the establishment of East Kalimantan as a new capital. This type of research is descriptive qualitative using interview and documentation methods. The findings of the research from the three regions studied are the municipalities of Palangka Raya, Katingan Regency and Gunung Mas Regency that the three regions have made some preparations in responding to the discourse of moving the capital as did the city of Palangka Raya in the form of building road expansion, expansion and renovation of city parks and expansion Airport area. While the Katingan district, is preparing candidates for airports, ports and areas of forest conservation, production forests, agriculture and offices. The same thing is also done by Gunung Mas who has poured in the regional spatial plan for 2014 - 2034, it can be said that the availability of land for the construction of office infrastructure and other development areas has shown adequate readiness and can meet the expectations of the community in service development, so that the availability of the land meets the expectations and discourse of moving the capital of the Republic of Indonesia to Gunung Mas Regency, Central Kalimantan.